2019
DOI: 10.21315/aamj2019.24.s1.8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Umra and Ruqba in Disbursement of Family Takaful Benefit: An Analysis From Shariah Perspective

Abstract: The paper aims to analyse the validity of practicing umra and ruqba concepts in disbursement of family takaful benefit from the shariah perspective. In the current practice of takaful, the disbursement of family takaful benefit is subject to the demise of takaful certificate holder. Upon maturity of the certificate, if the certificate holder is alive, he will enjoy takaful benefit but not the beneficiary or hibah recipient. Accordingly, he takes back the donation that he made earlier, which makes the arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hence, the proceeds will never return to the certificate holders as they are already dead. In this case, a certificate holder may say, “I am donating the benefits of my Takāful certificate as hibah al-‘umra to so and so, subject to my death and his/her survival upon my demise” (Rahman et al , 2019; SS#1, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the proceeds will never return to the certificate holders as they are already dead. In this case, a certificate holder may say, “I am donating the benefits of my Takāful certificate as hibah al-‘umra to so and so, subject to my death and his/her survival upon my demise” (Rahman et al , 2019; SS#1, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Later, Rahman et al (2018), in their analytical study on hibah al-'umra and ruqba in Islamic law, examined the possibility of their applications to solve the ownership and hibah issues of the family Tak aful benefits and suggested considering these types of hibah as the underlying ground for the survivorship principle in the joint tenancy arrangement. In a similar work, Rahman et al (2019) have thoroughly examined the prospect of applying hibah al-'umra and hibah alraqba principles and concluded that there is an enormous potential for applying these concepts in the disbursement of Tak aful benefits with a structured checklist form in IMEFM 16,1 policyholders' underwritings. However, all these previous works were theoretical and did not include any empirical study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…15 The application of conditional hibah in takaful has also been discussed by Md. Habibur et al 16 However, the authors in both articles did not discuss the effect of nomination for other nomination-based products such as the Pilgrimage Fund and Insurance and Employee's Provident Fund nor discuss the possibility of streamlining the nomination policy for all the nomination-based products. Therefore, there is a need to study the possibility of streamlining the nomination policy in Malaysia.…”
Section: Part I -Literature Reviewmentioning
confidence: 99%